PENGARUH DUKUNGAN UNIVERSITAS TERHADAP MINAT BERWIRAUSAHA - Julaicha, Julaicha; Marlena, Novi (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
Abstract This study aims to find out the effect of university support on the entrepreneurial intention among students at the Faculty of Economics and Business, State University of Surabaya. The population of this study were students of the Faculty of Economics and Business, State University of Surabaya class of 2019-2021 who had experienced curricular and co-curricular entrepreneurship support by the university. Then a sample of 102 students was taken using a purposive sampling technique. The data collection technique used an online questionnaire with google form. Data analysis used Partial Least Square (PLS) which was processed with Smartpls 3.2.9. The results of this study prove that there is a positive and significant influence from university support on entrepreneurial intention in students of the Faculty of Economics and Business, State University of Surabaya.